2007
DOI: 10.1590/s1980-57642008dn10200007
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural assessment of the dysexecutive syndrome (BADS) in healthy elders and Alzheimer´s disease patients: preliminary study

Abstract: Although the main initial deficit is considered to be in the memory domain, an early impairment of executive functions is also found in AD where these deficits are correlated to functional impairment. Ecological tests are more indicated to evaluate executive impairment, and are better able to assist in treating AD patients than more commonly used tests.ObjectivesThe aim of this preliminary study is to verify the performance in executive functions using the Behavioural Assessment of the Dysexecutive Syndrome (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
1
4
0
2
Order By: Relevance
“…However, three other subtests of the BADS suggested greater diagnostic sensitivity (rule shift cards, zoo map test, modified six elements subtest). Our results are consistent with other studies that found difficulties in planning and demonstrated a decline in performance on the six modified elements subtest 47 - 49 and zoo map test. 50 A difference was also seen on total scores, stan­dard, standard by age and overall classification by age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, three other subtests of the BADS suggested greater diagnostic sensitivity (rule shift cards, zoo map test, modified six elements subtest). Our results are consistent with other studies that found difficulties in planning and demonstrated a decline in performance on the six modified elements subtest 47 - 49 and zoo map test. 50 A difference was also seen on total scores, stan­dard, standard by age and overall classification by age.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study by Traykov et al 44 suggested that patients with MCI may be identified by using more detailed procedures rather than memory assessment alone and that patients with MCI present impairment to several aspects of executive functions. Canali, Brucki and Bueno 47 published the preliminary results from a study involving the BADS to verify executive function performance in healthy elderly patients with probable AD at initial phases, and the applicability of this ecological assessment in Brazil. They found differences among groups and confirmed the efficacy of the BADS in detecting executive deficits.…”
Section: Discussionmentioning
confidence: 99%
“…The Similarities subtest of the WAIS-III battery can be used for assessing abstraction ability (practice option). Notes - The Executive Interview EXIT-25, 117 , 118 Battery for Behavioral Assessment of the dysexecutive Syndrome (BADS) 119 , 120 and the Frontal Assessment Battery (FAB) 121 are currently undergoing the initial stage of validation in Brazil. …”
Section: Executive Functionsmentioning
confidence: 99%
“…Os resultados do modelo de regressão logística encontram-se na tabela 24. Rainville et al, 2002;Canali et al, 2007) e em pacientes com CCLa (Espinosa et al, 2009). Além disto, os resultados que encontramos apontam para um desempenho progressivamente comprometido de acordo com o diagnóstico de demência, sugerindo um continuum abrangendo sujeitos saudáveis, pacientes com CCLa e DA, dos quais os pacientes com DAPS, obtiveram comprometimento mais grave no desempenho.…”
Section: Resultados Do Modelo De Regressão Logísticaunclassified
“…Lincoln et al (2006). Julgamento temporal (julgamento temporal e pensamento abstrato) em acordo a outros estudos (Canali et al, 2007;Norris e Tate, 2000), não se mostrou útil para a diferenciação dos grupos, ratificando o que foi proposto por Wilson et al (1996) Nossos achados estão em acordo aos estudos de Espinosa et al (2009), Alegret et al Alguns modelos teóricos (Grafman, 1989;Shallice, 1982) Grigsby et al,1998;Sherod et al, 2009). Neste sentido, a diferenciação dos grupos é importante para a orientação e gestão das atividades da vida diária em pacientes com doenças degenerativas e em pacientes CCLa (Espinosa et al, 2009).…”
Section: Subtestes Da Badsunclassified